2017
DOI: 10.1002/dta.2232
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of new psychoactive substances and prescription drugs in the Belgian driving under the influence of drugs population

Abstract: Driving under the influence of drugs (DUID) is a worldwide problem. Several countries have adopted DUID legislations which prove their deterrent effect and impact on road safety. However, the use of new psychoactive substances (NPS) and prescription drugs is not known, as the applied roadside screening tests have not yet been adapted for these compounds. In this study, 558 blood samples obtained during roadside controls in Belgium (January to August 2015) after a positive Drugwipe 5S® test and 199 oral fluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 33 publications
(79 reference statements)
3
24
0
Order By: Relevance
“…Poly-drug abuse was also observed in many other retrospective studies. [17][18][19]21,22 In accordance with Tuv et al 18 and Wille et al 21 In contrast to previous studies determining the prevalence of NPS in DUID cases ( Another potential influence on the study's prevalence is the possible instability of NPS, particularly synthetic cathinones, in blood. [7][8][9][10][11][12][13][14][15] To reduce drug loss, many authors investigating the stability of NPS in blood recommended −20 C to be the best storage condition.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Poly-drug abuse was also observed in many other retrospective studies. [17][18][19]21,22 In accordance with Tuv et al 18 and Wille et al 21 In contrast to previous studies determining the prevalence of NPS in DUID cases ( Another potential influence on the study's prevalence is the possible instability of NPS, particularly synthetic cathinones, in blood. [7][8][9][10][11][12][13][14][15] To reduce drug loss, many authors investigating the stability of NPS in blood recommended −20 C to be the best storage condition.…”
Section: Discussionsupporting
confidence: 77%
“…17 Comparatively higher prevalence rates for stimulant designer drugs (21-28%) and synthetic cannabinoids (15-19%) were found in Hungary. 20 Recently, Wille et al 21 In our study, designer stimulants were found in two cases.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Screening for OcF metabolites was performed using a previously reported LC-HRMS method. 20,[25][26][27]32 LC-HRMS settings…”
Section: Lc-hrms Analysismentioning
confidence: 99%